STUDENTS’ LEARNING STRATEGIES IN LISTENING CLASS - Rhidwan, Silmi Fauziyah (English Education Department of STKIP Pasundan, 2019)
Most of students think that listening comprehension is not an easy activity to do. The problems because of the students’ levels in English proficiency. The level of students can have significant role when they listen to long parts and keep all information in their mind (Azmi Bingol, Celik, Yidliz, and Tugrul Mart, 2014). So many problems were found when they faced listening class; the study found that the students’ problems were the quality of recorded material and the length and speed in listening. The students’ strategies that the researcher found were storing and memory process and self-evaluating. There are only 4 students, out of 5, who used the listening learning strategies. The students have to interest listening comprehension. The researcher also found that students’ learning strategies can help the students to solve their problems in listening class.